Development of Intercity Rail Transit in China - LIANG Jianying; WANG Songwen; DING Sansan; WANG Xueliang; WANG Dong (机车电传动)
Current situation and future development of intercity rail transit in China was discussed and analyzed. The concept, characteristics, function and pattern of intercity rail transit was summarized, as well as the necessity and urgency for developing the intercity rail transit, and general view of development trend for the future intercity mass transit was put forward.